2019
DOI: 10.1038/s41598-018-37098-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between dopaminergic and non-dopaminergic neurons in the VTA following chronic nicotine exposure during pregnancy

Abstract: Exposure to nicotine during pregnancy through maternal smoking or nicotine replacement therapy is associated with adverse birth outcomes as well as several cognitive and neurobehavioral deficits. Several studies have shown that nicotine produces long-lasting effects on gene expression within many brain regions, including the ventral tegmental area (VTA), which is the origin of dopaminergic neurons and the dopamine reward pathway. Using a well-established rat model for perinatal nicotine exposure, we sought to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 48 publications
0
26
0
Order By: Relevance
“…Following perinatal nicotine–alcohol treatment contrasted against the alcohol group, 2,113 genes were upregulated and 1,836 were downregulated. Statistical analysis was done using Benjamini and Hochberg (BH) method with q value < 0.05 and an absolute log2 fold change > 1 as previously described in Keller et al 31 , 32 . Figure 1 illustrates the heatmaps of the top 50 significantly differentially expressed miRNAs (DEmiRs) following perinatal (a) alcohol and (b) nicotine–alcohol exposures compared to the saline control group, and (c) nicotine–alcohol exposure compared to the alcohol treatment group.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Following perinatal nicotine–alcohol treatment contrasted against the alcohol group, 2,113 genes were upregulated and 1,836 were downregulated. Statistical analysis was done using Benjamini and Hochberg (BH) method with q value < 0.05 and an absolute log2 fold change > 1 as previously described in Keller et al 31 , 32 . Figure 1 illustrates the heatmaps of the top 50 significantly differentially expressed miRNAs (DEmiRs) following perinatal (a) alcohol and (b) nicotine–alcohol exposures compared to the saline control group, and (c) nicotine–alcohol exposure compared to the alcohol treatment group.…”
Section: Resultsmentioning
confidence: 99%
“…Following nicotine–alcohol exposure 5 miRNAs were upregulated and 8 were downregulated when compared to the alcohol treatment group. The BH method was used for the statistical analysis applying parameters of q value < 0.05 and an absolute log2 fold change > 0.5 as previously described in Keller et al 31 , 32 . Table 2 a–c list the most significant up and downregulated DEGs along with their description and predicted miRNA targets for perinatal alcohol, nicotine–alcohol and nicotine–alcohol vs. alcohol treatment groups, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We recently investigated the influence of maternal nicotine intake on genetic pathways of VTA DA and non-DA neurons in rat pups 33 . Our results showed that the extracellular matrix (ECM) receptor interactions were significantly altered in both DA and non-DA neurons.…”
Section: Introductionmentioning
confidence: 99%